IMPLEMENTASI POLA TATA RUANG DESA PESISIR DI KABUPATEN BANGKA SELATAN (STUDI KASUS DESA TUKAK) - Wahyu Adi; Dwi Riska Zulkia; Kurniawan Salim; Aditya Pamungkas (Akuatik: Jurnal Sumberdaya Perairan, 2019)
This study aims to find out how the suitability of urban planning implementation in the South Bangka Regency (Study Case at Tukak Coastal Village) based on Government Spatial Plan (RTRW). The research method used is descriptive qualitative method. Data analysis will be carried out by using the survey results in the form of a questionnaire to find out community perceptions regarding regional spatial patterns in Tukak Village, analyzing the suitability of spatial use with the South Bangka Regency RTRW and the drivers of land change. The survey results will also be used to determine the level of land suitability in Tukak Village and analyzed using GIS (Geographic Information System). The research instruments that will be used in the analysis are observation, ground check, interviews, documentation, and data processing using the GIS application. From the results of research that has been done, it is known that in the implementation of spatial patterns in Tukak Village there are about 1,904.33 ha of land use in Tukak Village which is not in accordance with the District Spatial Plan. South Bangka. Good socialization and understanding of spatial planning has not been thoroughly obtained by the community and they support the evaluation of the layout of the Tukak Village in accordance with the District Spatial Plan. South Bangka.